Tingkat Kepercayaan Masyarakat Terhadap Cryptocurrency Sebagai Alat Investasi - Kadek Srestiyani; Putu Sri Arta Jaya Kusuma (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
Apart from conventional currency, Cryptocurrency can also be used as an investment asset. However, Cryptocurrency is famous for its high level of volatility, where this investment can produce large profits and losses in a short time. Seeing this opportunity, many people are starting to be interested in investing in this instrument. Various responses and assessments have developed in society regarding this investment, especially in Indonesia. At the beginning of its appearance, people were skeptical about the results offered. And quite a few also assume that this investment is nothing more than a fraudulent scheme. However, as time goes by, and as information spreads easily, people begin to understand and believe in this type of investment and start investing on a small to massive scale. Even now, some people still believe that Cryptocurrency investment is a scam. This research aims to collect data on how much trust the Indonesian people have in investing in Cryptocurrency. This research method uses a quantitative method, namely using primary data in the form of a questionnaire distributed to the people of Denpasar City. With a population of 30 people and a sample calculated using the Slovin formula of 30. Based on this research, the level of trust has no significant effect on cryptocurrency as an investment tool. There are many factors that influence people's confidence in investing in cryptocurrencies.